2010
DOI: 10.2478/s11536-009-0025-6
|View full text |Cite
|
Sign up to set email alerts
|

An increase of elastic tissue fibers in blood vessel walls of placental stem villi and differences in the thickness of blood vessel walls in third trimester pre-eclampsia pregnancies

Abstract: AbstractThis study has goals of examining whether pre-eclampsia may lead to an increase of elastic tissue fibers in blood vessel walls of placental stem villi or whether there are differences in the thickness of blood vessel walls within these villi when compared to normotensive pregnant women. Non-infarcted placental tissue samples from 28 participants with uncomplicated pregnancies and 26 patients with pre-eclampsia were obtained. After routine histological procedures, the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Wareing et al also reported increased chorionic venous contractility induced by hypoxia in IUGR but not in normal pregnancy (Wareing et al, 2006 ). Furthermore, previous studies reported that placental terminal villi thickness was increased in mouse (Hvizdošová-Kleščová et al, 2013 ) and in human placenta from IUGR pregnancy (Mayhew et al, 2003 ), and elastic fibers in IUGR placenta blood vessels were found to be reduced (Wilhelm et al, 2002 ) but increased in PE pregnancy (Baran et al, 2010 ). Collectively, their results suggested that the vascular stiffness/compliance might have altered in disease and it could affect the blood flow hemodynamics in fetoplacental circulation.…”
Section: Placentamentioning
confidence: 96%
“…Wareing et al also reported increased chorionic venous contractility induced by hypoxia in IUGR but not in normal pregnancy (Wareing et al, 2006 ). Furthermore, previous studies reported that placental terminal villi thickness was increased in mouse (Hvizdošová-Kleščová et al, 2013 ) and in human placenta from IUGR pregnancy (Mayhew et al, 2003 ), and elastic fibers in IUGR placenta blood vessels were found to be reduced (Wilhelm et al, 2002 ) but increased in PE pregnancy (Baran et al, 2010 ). Collectively, their results suggested that the vascular stiffness/compliance might have altered in disease and it could affect the blood flow hemodynamics in fetoplacental circulation.…”
Section: Placentamentioning
confidence: 96%
“…89,90 The result is a prothrombotic and hypofibrinolytic state that increases the risk of placental thrombosis and fetal growth restriction. [91][92][93][94] Preeclampsia is characterized by shallow trophoblast invasion and, later on, by an increased elastin content in placental villi, 95 two pathogenetic mechanisms that affect the conversion of high-resistance to low-resistance vessels. Trophoblast invasion and elastolysis are mediated by matrix metalloproteinase-9 that is cleaved from a precursor by plasminogen activators.…”
Section: Preeclampsiamentioning
confidence: 99%